Effect of blood pressure on mortality in patients with cognitive impairment: a prospective cohort study - Shang, YanChang; Wang, ShuHui; Wei, Chao; Gao, ZhongBao; Xie, HengGe; Wang, ZhenFu (Frontiers in Cardiovascular Medicine, 2023)
Background Cognitive impairment is a prevalent condition that substantially elevates mortality rates among the elderly. The impact of hypertension on mortality in older adults with cognitive impairment is a subject of contention. This study aims to examine the influence of hypertension on both all-cause and CVD-specific mortality in elderly individuals experiencing cognitive impairment within a prospective cohort. Methods This study encompassed 2,925 participants (weighted 53,086,905) aged 60 years or older from National Health and Nutrition Examination Survey (NHANES) spanning 2011–2014. Incidence of all-cause and CVD-specific mortality was ascertained through linkage with National Death Index records until 31 December 2019. Survival was performed employing the Kaplan–Meier method. Hazard ratios (HRs) were calculated via Cox proportional hazards regression models. Results Over the follow-up period of up to 9.17 years [with a median (IQR) time to death of 6.58 years], equivalent to 18,731.56 (weighted 3.46 × 108) person-years, there were a total of 576 recorded deaths. Participants with CI exhibited a 1.96-fold higher risk of all-cause mortality (95% CI: 1.55–2.49; p < 0.01) and a 2.8-fold higher risk of CVD-specific mortality (95% CI: 1.83–4.29; p < 0.01) in comparison to participants without CI. Among participants with CI, concurrent hypertension comorbidity was linked to a 2.73-fold elevated risk of all-cause mortality (95% CI: 1.78–4.17; p < 0.01) and a 5.3-fold elevated risk of CVD-specific mortality (95% CI: 2.54–11.04; p < 0.01). Further stratified analyses revealed that the combined effects of hypertension and CI on all-cause and CVD-specific mortality were more pronounced in participants aged 60–69 years compared to those aged 70–80 years (p for interaction <0.01). The primary findings exhibited resilience across a series of sensitivity analyses. Conclusions Participants with CI exhibited a markedly elevated risk of all-cause and CVD-specific mortality when coexisting with hypertension. Appropriate management of hypertension in patients with CI may be helpful in reducing the excess risk of death.